1999
DOI: 10.1109/7.784070
|View full text |Cite
|
Sign up to set email alerts
|

MMW radar scattering statistics of terrain at near grazing incidence

Abstract: The statistical behavior of clutter observed near grazing incidence and at 95 GHz is investigated for the specific cases of bare ground, snow-cover, and for a heterogeneous scene. The bare ground constitutes a homogeneous target under homogeneous conditions and the magnitude of the amplitude is Rayleigh distributed. While the snow-cover is a homogeneous target, the conditions under which it was observed are heterogeneous, and the Bayes rule is employed to describe its clutter distribution. The Bayes rule integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In each realization, both the locations of the point target and the clutter response are randomly assigned. In recent studies [8,9], it was demonstrated that at near grazing incidence the MMW radar backscatter response of statistically homogeneous clutter complies with the Rayleigh statistical model. In other words, the phase of the scattered field is uniformly distributed and its power obeys an exponential probability density function (completely defined by its mean value).…”
Section: A Numerical Simulation Proceduresmentioning
confidence: 73%
“…In each realization, both the locations of the point target and the clutter response are randomly assigned. In recent studies [8,9], it was demonstrated that at near grazing incidence the MMW radar backscatter response of statistically homogeneous clutter complies with the Rayleigh statistical model. In other words, the phase of the scattered field is uniformly distributed and its power obeys an exponential probability density function (completely defined by its mean value).…”
Section: A Numerical Simulation Proceduresmentioning
confidence: 73%
“…Once the image clutter distribution is known and an acceptable false-alarm rate chosen, a threshold value for the detectability of a target of a given RCS can be determined. For a statistically homogeneous terrain scene, in the absence of multipath and shadowing effects, the scattered field response (i.e., equivalently, the amplitude of the scattering matrix elements, |S pq |, or radar voltage response) is commonly found to conform to Rayleigh statistics (58). In other words, the real and imaginary parts of S pq are observed to be uncorrelated zero-mean Gaussian random variables with equal variances.…”
Section: Resultsmentioning
confidence: 99%
“…It is common to model a complex valued radar image as linear in the target with additive Gaussian distributed clutter. Examples where a Gaussian model is justified for terrain clutter can be found in [17]. Even in cases when such a model is not applicable to the raw data, a whitening and local averaging technique can be implemented to obtain a Gaussian approximation [13].…”
Section: Letmentioning
confidence: 99%
“…Similarly to (16), the same scaling factor captures the common amplitude in both regions. With the partition in (13), the maximal invariant [7] under the group of transformations in (23) is composed of and in (17), and…”
Section: ) Casementioning
confidence: 99%